Plant and snail communities in three habitat types in a limestone landscape in the west of Ireland, and the effects of exclusion of large grazing animals - Long, Maria P. (Trinity College (Dublin, Ireland). Department of Botany, 2011)
This thesis documents the plant and snail communities found in woodland, scrub and grassland in the Burren region in the west of Ireland. The flora of the Burren is renowned and has been well studied, but the vegetation communities are less well understood. In relation to molluscs, their distribution in Ireland is quite well documented, but studies on molluscan ecology and community structure are lacking, particularly for land snails. Additional work with the molluscan data includes an examination of the population structure and an assessment of methodological issues. This thesis also investigates experimentally the short term changes in plant and snail communities following cessation of grazing by large herbivores. This study is exceptional in assessing the effects of grazing by looking at multiple habitats using a replicated, balanced multisite design. The project design enables the study of ecological change on a number of scales – quadrat, site, habitat and landscape. Scrub encroachment is a big issue for many land owners and managers in the Burren, with hazel, Corylus avellana, being the most significant species involved. The woodland and scrub habitats selected for study were hazel-dominated, and all of the grasslands had hazel scrub nearby. The findings of the vegetation study indicate that, unsurprisingly, the vegetation of woodlands and grasslands differ substantially, with soil fertility as well as light penetration being important in the separation. Interestingly, the scrub vegetation differed floristically from both woodland and grassland. Further, it could be split into two distinct subsets – ‘woody’ and ‘grassy’. These elements formed reasonably distinct entities which were related to the woodland and grassland vegetation communities respectively, but were distinct from either. A total of 30 species of snail was recorded, which is approximately 45% of the total number of land snails in Ireland. This included a number of species from the ‘Red List’ for Irish non-marine molluscs. The woodlands and scrub had higher abundances of snails and were more species rich than the grasslands. The amount of litter in a quadrat was found to be an important factor correlated with species richness of snails, while plant species richness was not found to be correlated with snail richness. With regard to population structure of snails, the populations at the study sites were shown to be composed mainly of juveniles, with only 28% adults. The inclusion of dead and immature individuals in the results added six to the species list, but these species occurred in very low numbers. The relative abundances of species was shifted, however, if only adults were included. The advantages of using a 0.5mm sieve mesh size for processing samples were shown by the large numbers of snails found in this smaller size fraction and by the demonstration that a number of species are underestimated when sampling using a 1mm sieve mesh. However, these advantages need to be weighed against the benefits gained in terms of decreased lab work time. The changes in the vegetation brought about by the cessation of grazing were rapid and dramatic in the grasslands. Many plant species declined in abundance and several flowering plant species disappeared. There was a major build-up of litter, and cover of grasses increased significantly. Both diversity and species richness of plants decreased. The woodlands presented contrasting findings to the grasslands, with plant diversity increasing significantly. Species richness increased also, although the change was not statistically significant. The amount of bare earth decreased sharply, and the cover of field layer plants increased in parallel. There was little detectable pattern of change in the scrub vegetation; this can be ascribed to the heterogeneity and variability of the habitat and the restricted timeframe of the 24-month study period. A large change was seen in the snail communities in the grasslands in this case, abundance and species richness increased. The changes were linked with the litter build-up, and the denser, taller vegetation within the fenced plots. Few individual species showed strong trends, with the pattern instead being a small and variable, but relatively consistent, increase across all species. The snail communities showed little appreciable changes in the woodlands and scrub during the timespan of this survey. Again, a period of 24 months may not have been long enough for measurable changes to manifest themselves. Land abandonment is a major threat in many ecosystems and the cessation of existing management regimes (e.g. grazing) is likely to have a large impact on plant and animal communities. Changes have been seen in the Burren in recent decades, with perhaps the most dramatic example being the expansion of hazel scrub. This has been attributed mainly (though not exclusively) to changes in grazing practices. The network of fenced exclosures, and their associated control plots, set up during this project are an important resource for the study and documentation, now and in the future, of how changing management practices are affecting plant and animal communities. Already, the loss of some plant species has been documented from grasslands in the absence of grazing, indicating how essential grazing is for the maintenance of semi-natural grasslands in the region. However, this loss of diversity is offset by the success of the snails in the ungrazed plots, reminding us that solutions are rarely straightforward in conservation management, and that a variety of structural elements (e.g. grazed and ungrazed patches) is probably optimal for biodiversity.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin